A Proposal for a Unifying Set of Definitions of Fatigue - Skau, Simon; Sundberg, Kristoffer; Kuhn, Hans-Georg (Frontiers in Psychology, 2021)
In this paper, we propose a set of unifying definitions that are useful in all areas of fatigue research while remaining neutral to the various theories about fatigue. We first set up two criteria and four desiderata that a definition for interdisciplinary use needs to fulfill: (i) non-circularity, (ii) finiteness, (iii) broadness, (iv) precision, (v) neutrality, and (vi) phenomenon-focus. We argue that other existing attempts to unify definitions within fatigue research do not fulfill all of these criteria and desiderata. Instead, we argue for a set of stipulative definitions, centered around performance measures and subjective estimations, is required in order to maximize clarity. In total, a set of 13 distinct definitions of fatigue and fatigue-related phenomena is presented. These definitions will help facilitate communication between different researchers, link phenomena from divergent research fields together, facilitate application and knowledge production, and increase the specificity for hypothesis testing.